The Relationship Between Environmental Quality And HumanDevelopment: Study In Malang City - Nurhasan, Hadhori; Afifah, Dian Annisa (PANGRIPTA, 2024)
This research investigates the negative impact of uneven economic growth and high levels of poverty on the human development index on the island of Java, with Malang City as the focus. This phenomenon indicates that there is inequality in human development in the region. This research aims to understand the relationship between natural resources, the environment and the economy by using IKLH and spending on environmental protection functions as proxy variables. This research method uses qualitative and involves analysis of statistical data obtained from tables presenting Malang City IKLH, human development index, and poverty data during the research period. The research results show that fluctuations in the IKLH of Malang City indicate serious challenges in maintaining the quality of the environment in the city. In addition, high levels of poverty are an obstacle to efforts to increase human development. Therefore, this research recommends the need for more targeted and sustainable policies in overcoming the negative impacts of uneven economic growth and high levels of poverty. Concrete steps, such as strengthening basic infrastructure, increasing access to education and health services, and developing targeted social assistance programs, are proposed as solutions to overcome these problems.